Groups in context : leadership and participation in small groups - Wilson, Gerald L., 1943- (McGraw-Hill, 1996)
"Intended for the introductory course in group communication, Groups in Context is a well-balanced blend of theory and applications that gives students an abundant amount of real-life examples to help them translate pertinent principles and concepts into actual group situations. The fourth edition has been fully updated and now has a stronger emphasis on gender and diversity issues that affect group interaction. New to this edition are "A Question of Ethics and Responsibility" boxes and "Focus on Research" boxes."--BOOK JACKET.